To study the effect of monosodium glutamate on histomorphometry of cortex of kidney in adult albino rats. (March 2014) - Dixit, Shilpi Gupta; Rani, Puja; Anand, Akansha; Khatri, Kamlesh; Chauhan, Renu; Bharihoke, Veena
Abstract Thousands of chemicals are being used recently in our new high tech foods like ready to eat Japanese, Chinese, packaged and tinned foods. Most food additives act as either preservatives or flavor enhancers like monosodium glutamate (MSG), a sodium salt of glutamic acid. The present study investigated the effect of intraperitoneally administered MSG on cortex of the kidneys of adult albino Wistar rats and compared with control group. The histomorphometry done by calibrating with ocular micrometer on kidney tissue of control and experimental group revealed a significant difference in glomeruli with increase in length, size of bowman's capsule with an increase in bowman's space. The size of renal tubules could not be compared as the cells of these tubules in experimental group were disintegrated and distorted. In the experimental group (rats treated with 4 mg MSG/g body weight), the cortex of the kidneys developed variable pathological changes, which were patchy in distribution with intervening normal areas. There was distortion of renal cytoarchitecture. Many glomeruli (66.4%) showed hypercellularity, i.e., cellular proliferation of mesangial or endothelial cells and infiltration of inflammatory cells. The capillary membrane showed thickening as was evident on PAS stain. Since MSG, as a food additive, was found to be toxic on various organs of the body by various researchers, it should perhaps be stopped from being used as a food additive. This may be a suggestion which needs validation in human studies.